An astrophysical interpretation of the remarkable g-mode frequency groups of the rapidly rotating γ Dor star, KIC 5608334. Issue 2 (29th March 2018) - Saio, Hideyuki; Bedding, Timothy R; Kurtz, Donald W; Murphy, Simon J; Antoci, Victoria; Shibahashi, Hiromoto; Li, Gang; Takata, Masao
Abstract: The Fourier spectrum of the γ-Dor variable KIC 5608334 shows remarkable frequency groups at ∼3, ∼6, ∼9, and 11–12 d −1 . We explain the four frequency groups as prograde sectoral g modes in a rapidly rotating star. Frequencies of intermediate-to-high radial order prograde sectoral g modes in a rapidly rotating star are proportional to | m | (i.e. ν ∝ | m |) in the corotating frame as well as in the inertial frame. This property is consistent with the frequency groups of KIC 5608334 as well as the period versus period-spacing relation present within each frequency group, if we assume a rotation frequency of 2.2 d −1, and that each frequency group consists of prograde sectoral g modes of | m | = 1, 2, 3, and 4, respectively. In addition, these modes naturally satisfy near-resonance conditions ν i ≈ ν j  + ν k with mi  =  mj  +  mk . We even find exact resonance frequency conditions (within the precise measurement uncertainties) in many cases, which correspond to combination frequencies.